A conjectura de Lazer-McKenna para problemas de Ambrosetti-Prodi - Silva, Maria do Desterro Azevedo da (2012)
In this paper, we study questions related to the existence and multiplicity of solutions to problems of Ambrosetti-Prodi type. We present the conjecture of Lazer- McKenna, checking its validity in the one dimensional case. To obtain our results, we use essentially topological, variational and sub and supersolution methods.